Gamificação de disciplinas de Química nos ensinos médio e superior - Castro, Guilherme de Lima (2024)
In the last decades, education has been reflecting on effective methodological processes for the teaching and learning of Chemistry, aiming to break away from purely traditionalist practices and experiences. This thesis discusses the proposal of the active methodology gamification, which incorporates game design elements such as mechanics, dynamics, and enjoyment, providing high-performance experiences and engagements for the involved subjects. The applicability of gamification is favored in multiple aspects, such as adaptability to various learning styles, motivational incentives by integrating challenges and rewards, real-world simulations that enhance the development of critical thinking skills and problem-solving abilities. In essence, this methodology brings a dynamic, creative, and effective approach to inspire students to cultivate a deeper appreciation for the discipline, consequently fostering active learning. This thesis reflects and presents approaches to the importance of gamification in and for the teaching and learning of Chemistry, emphasizing the scarcity of publications on the subject. The overall objective is to develop the gamification of the Organic Chemistry I discipline at the Federal University of Ceará (UFC) and in two quarters of the mentioned discipline in High School at the EEMTI Deputado Paulino Rocha school, both in Fortaleza-CE, aiming to increase engagement and enhance the learning process. This research has both qualitative and quantitative aspects and was applied in Higher Education and High School modalities. Mechanics such as attendance and punctuality, pre-recorded video lessons, Surprise Tests (top test), social networks, game apps, group tasks, and awards for students who excelled in the ranking were used in these teaching modalities. However, some mechanics differed in adaptability to the levels. As the research progressed, new mechanics were incorporated, such as the use of Kahoot and the creation of the board game "Viking Invasion." The results obtained were interesting and inspired future research within the research group itself. The implementation of gamification is a clear positive factor that stimulates interest, promotes engagement, and favors the transformation of the educational environment. This work contributes significantly to the consolidation of gamification as a methodological strategy in the teaching and learning of Chemistry, opening doors for innovative educational investigations and projects.